Radiation budget in greeen beans crop with and without polyethylene cover - de Souza, José Leonaldo; Escobedo, João Francisco (Pesquisa Agropecuaria Brasileira, 1997)
The radiation budget in agricultural crops is very important on the microclimate characterization, on the water losses determination and on dry matter accumulation of vegetation. This work describes the radiation budget determination in a green beans crop (Phaseolus vulgaris L.), in Botucatu, SP, Brazil (22o 54'S; 48o 27'W; 850 m), under two different conditions: the normal field culture and in a polyethylene greenhouse. The densities of fluxes of radiation were used to construct diurnal curves of the components of global radiation (Rg), reflected radiation (Rr), net radiation (Rn).The arithmetic's relations allowed to obtain the components net short-waves (Rc) and net long-waves (Rl). The analysis of these components related to the leaf area index (LAI) in many phenological phases of the culture showed Rg distributed in 68%, 85%, 17% and 66%, 76%, 10% to Rn, Rc, and Rl, in the internal and external ambients in a polyethylene greenhouse, respectively.
Keywords: solar radiation; greenhouse; Phaseolus vulgaris; microclimate